2022
DOI: 10.1007/s12598-021-01959-y
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of CO2 oxidative dehydrogenation of propane to propylene over Cr-free metal catalysts

Abstract: CO 2 -assisted oxidative dehydrogenation of propane (CO 2 -ODHP) is an attractive strategy to offset the demand gap of propylene due to its potentiality of reducing CO 2 emissions, especially under the demands of peaking CO 2 emissions and carbon neutrality. The introduction of CO 2 as a soft oxidant into the reaction not only averts the over-oxidation of products, but also maintains the high oxidation state of the redox-active sites. Furthermore, the presence of CO 2 increases the conversion of propane by cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 160 publications
0
21
0
Order By: Relevance
“…1,11,30 However, due to the toxic and carcinogenic properties of Cr(VI) oxides, it is vital to find alternatives. 30 Group IIIA mixed oxides such as Ga 2 O 3 −Al 2 O 3 31,32 and In 2 O 3 −Al 2 O 3 33 and supported In 2 O 3 catalyst 25,34 show comparable catalytic performance as well. On Ga 2 O 3 , ODHP is proposed to proceed via the heterolytic propane dissociation on acid−base pairs, namely, Ga δ+ −O 2− pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,30 However, due to the toxic and carcinogenic properties of Cr(VI) oxides, it is vital to find alternatives. 30 Group IIIA mixed oxides such as Ga 2 O 3 −Al 2 O 3 31,32 and In 2 O 3 −Al 2 O 3 33 and supported In 2 O 3 catalyst 25,34 show comparable catalytic performance as well. On Ga 2 O 3 , ODHP is proposed to proceed via the heterolytic propane dissociation on acid−base pairs, namely, Ga δ+ −O 2− pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing catalysts that can selectively break the C–H bond to produce alkenes while suppressing PDR is of great interest. Similar to the O 2 -ODHP route, redox-active metal oxides (Cr and V) are promising candidates for CO 2 -ODHP. ,, However, due to the toxic and carcinogenic properties of Cr­(VI) oxides, it is vital to find alternatives . Group IIIA mixed oxides such as Ga 2 O 3 –Al 2 O 3 , and In 2 O 3 –Al 2 O 3 and supported In 2 O 3 catalyst , show comparable catalytic performance as well.…”
Section: Introductionmentioning
confidence: 99%
“…To better address this challenge, Wang et al [111] reported PtSn/SiO 2 catalysts with the addition of CeO 2 as a promoter, which could improve the catalytic activity and selectivity. As in previous studies, [15,112] CeO 2 with high oxygen storage capacity and abundant oxygen defects was chosen to activate CO 2 . However, in this study, the order of the catalytic activity (PtSn/SiO 2 < PtCe/SiO 2 < PtSnCe/SiO 2 ) could be explained simply by the grain size and metal dispersion.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
“…Furthermore, the development of metal-catalyzed CO 2 À ODP is just in its infancy. Although several review papers have summarized CO 2 À ODP reactions in recent years, they have mainly focused on the role of CO 2 [12,15] and the mechanistic differences among various metal oxides [13,[16][17][18][19][20] but rarely on the catalytic performance and design concept of metallic catalysts. Therefore, we summarized and compared the trends in the catalytic performance of the reported metal oxide-and metalbased catalysts in terms of CO 2 versus C 3 H 8 conversion (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…High CO 2 partial pressures tend to mitigate coke formation, which is believed to result from the reverse Boudouard reaction (C + CO 2 → 2CO). ,,, Excess CO 2 is believed to enable the MvK reaction pathway by providing sufficient oxygen through CO 2 . Laboratory-scale experiments typically use 0.1 ≤ C 3 H 8 /CO 2 ≤ 0.5. , However, high CO 2 fractions up to C 3 H 8 /CO 2 = 1/20 were also studied .…”
Section: Introductionmentioning
confidence: 99%